Risk induced farmers’ participation in agricultural innovations: evidence from a field experiment in eastern Ethiopia - Sisay Diriba Lemessa; Molla Alemayehu Yismaw; Mulugeta Damie Watabaji (Development Studies Research, 2019)
It is widely accepted that agricultural innovations are vital to ensure food security and economic development. While farmers are among the key sources of agricultural innovations, many studies conducted in the past conceived them as adopters of externally generated technologies. They regarded farmers only as adopters of induced technologies. This study is designed to analyze farmers’ participation in agricultural innovation activities using survey and experimental data. Both descriptive and econometric techniques were employed to analyze the data. It appears that risk attitudes and time preferences are variables that enhance farmers’ participation in agricultural innovation activities. Wealth and socioeconomic variables such as access to information and irrigation facilities, input usage and age of household head are significantly correlated with farmers’ participation in agricultural innovation activities. The findings comply with the induced innovation hypothesis, which recognizes the importance of threats and opportunities to triggering farmers’ participation in agricultural innovation activities.